Wood and earth fortresses of the Teutonic Order in the territory of north-eastern Poland - Dariusz Poliński (Fasciculi Archaeologiae Historicae, 2015)
The following article is a discussion on wood and earth fortresses of the Teutonic Order in north-eastern Poland. It is simultaneously an attempt at organising information about less known facilities, their forms and application of building materials, as well as their function and chronology. Source data for these fortresses is not widely known or very laconic, mostly derived from mentions in written sources. 16 fortalices are discussed, seven of which were situated in the former territory of the Bartians or its border, five in the Galindians’ land, three in the Pogesanians’ area, and one in the Sassinians’ territory. It was noticed that fortresses constructed in the 14th century from scratch prevailed. Other fortalices were built, or were in most cases adapted for the Order’s needs as early as the 13th century. A part of the analysed fortresses functioned in the administration-territorial system within the framework of the Teutonic reign in Prussia. They were seats of the Order’s officials, mostly those of lower ranks: bailiffs, procurators and reeves. As far as the form of the discussed type of fortress is concerned, the most important data was provided by the facilities in Pisz and Szestno, situated in the former territory of the Galindians. Finally, it should be emphasised that in further studies on the issue of Teutonic wood and earth fortresses the most important and key role must be played by archaeological research.